Social support mediates the relationship between self-disclosure and benefit finding in patients with permanent intestinal ostomy due to colorectal cancer - Guo Chenxi; Zhou Caihong; Teng Zhiyu; Li Ling (结直肠肛门外科)
[Objectives] To investigate the levels of self-disclosure, social support, and benefit finding in patients with permanent intestinal ostomy due to colorectal cancer. Additionally, the research aimed to explore the mediating effect of social support between self-disclosure and benefit finding. [Methods] A survey was conducted among 253 patients with permanent intestinal ostomy due to colorectal cancer, who were receiving treatment at three tertiary hospitals in Changsha. The Painful Disclosure Scale, Social Support Evaluation Scale, and Benefit Finding Scale were utilized to gather data. [Results] The study revealed the following total scores among patients with permanent intestinal ostomy due to colorectal cancer: self-disclosure (32.0±7.0) points, social support (37.4±5.3) points, and benefit finding (58.1±13.3) points. Statistically significant differences were observed in the total scores of benefit finding across various factors, including age, marital status, occupation, educational level, family per capita monthly income, treatment plans, and disease courses of permanent intestinal ostomy due to colorectal cancer (P < 0.05). Furthermore, positive correlations were found between self-disclosure, social support, and benefit finding in patients with permanent intestinal ostomy due to colorectal cancer (P < 0.01). Similarly, a positive correlation was identified between social support and benefit finding (P < 0.01). Utilizing a mediating effect model, the study determined that social support partially mediated the relationship between self-disclosure and benefit finding in patients with permanent intestinal ostomy due to colorectal cancer. The mediating effect value was calculated as 0.3051, accounting for 37.91% of the total effect. [Conclusion] Patients with permanent intestinal ostomy due to colorectal cancer exhibited low levels of self-disclosure and benefit finding, along with moderate levels of social support. The study demonstrated that self-disclosure had a direct influence on benefit finding and also an indirect effect through social support. Timely intervention by medical staff is recommended to improve patients’ self-disclosure and social support levels, thereby promoting their benefit finding.